Foundations for a national assessment of soil biodiversity - Carlos A. Guerra; Nico Eisenhauer; Christoph C. Tebbe; Willi E. R. Xylander; C. Albert; Doreen Babin; Bartosz Bartkowski; Benjamin Burkhard; Juliane Filser; Dagmar Haase; Karin Hohberg; Janina Kleemann; et al. (Journal of Sustainable Agriculture and Environment)
Abstract Soils, just like all other ecosystem compartments, change over time and, consequently, conditions for soil‐inhabiting organisms are also changing, affecting their composition and diversity. Soil biodiversity is a critical component of ecosystems that supports many essential ecosystem functions and services, such as nutrient cycling, carbon sequestration, water regulation and biomass production for food, fodder, fibre and energy. However, and despite the importance of soil biodiversity for ecosystem health and human well‐being, neither current state, drivers, potential consequences for ecosystem services nor options for sustainable governance of soil biodiversity are well understood. Here, we provide a framework for and argue that conducting a national assessment of soil biodiversity, albeit being a complex endeavour, is fundamental to building a baseline to understand the current state and trends of soil biodiversity, but also to identify the main drivers of change, the impacts of soil biodiversity loss and the potential pathways for conservation and sustainable governance of soil biodiversity.